Decomposing the inequalities in the catastrophic health expenditures on the hospitalization in India: empirical evidence from national sample survey data - Sriram, Shyamkumar; Verma, Veenapani Rajeev; Gollapalli, Pavan Kumar; Albadrani, Muayad (Frontiers in Public Health, 2024)
India is characterized by one of the highest OOPE on healthcare, in conjunction with the pervasive socio-economic disparities entrenched in the population. As a corollary, India has embarked on the trajectory of ensuring financial risk protection, particularly to the poor with the launch of various flagship initiatives. This study was conducted to estimate the income-related inequalities in the incidence of CHE on hospitalization and glean the individual contributions of wider socio-economic determinants in influencing these inequalities in India.The study employed cross-sectional data from nationally represented survey on morbidity and healthcare (75 th round of NSSO) conducted during 2017-18 which circumscribed a sample size of 1,13,823 households (5,57,887 individuals). The inequalities and need-adjusted inequities in the incidence of CHE on hospitalization care was assessed via Erreyger's corrected concentration index. Need standardized concentration indices were further used to unravel the inter and intra-regional income related inequities in outcome of interest. Factors associated with the incidence of CHE was explored using Multivariate Logit Regression within the framework of Andersen's model of Behavioral health. Our findings revealed pervasive wealth-related inequalities in the CHE for hospitalization care with a profound gap between the poorest and richest income quintile. The negative value of concentration index (EI: -0.19) indicated the inequalities to be significantly concentrated amongst the poor. Multivariate logit results indicated that households with elderly, smaller size, vulnerable caste affiliation, poorest income quintile, no insurance cover, hospitalization in private facility, longer hospital stay duration and residence in regions at lower level of epidemiological transition level was associated with increased likelihood of incurring CHE on hospitalization. Decomposition analysis unraveled that the contribution of non-need/illegitimate factors (127.1%) in driving the inequality was positive and relatively high vis-à-vis negative low contribution of need/legitimate factors (35.3%). Most of the inequality was driven by the illegitimate factors which are amenable to policy change. Thus, policy interventions such as increasing the awareness, enrollment, and utilization of Publicly Financed Health Insurance schemes, strengthening the public hospitals to provide improved quality of specialized care and referral mechanism and increasing the overall budgetary share of healthcare to improve the institutional capacities is suggested.